Bridging wireless protocols. - Noerenberg, J.W., II (IEEE Communications magazine)
The lingua franca of the Internet is TCP/IP, and wireless devices are learning to speak this language. But what is the ?wireless Internet?? There are a number of different answers to this question. The question poses problems for equipment manufacturers, service providers, and users alike. We desire seamless access to the Internet, and in order to have that, all these different modes must operate transparently for users. This article discusses how TIA/EIA standard IS-856 cellular data (1×EV) can be married with IEEE 802.11b wireless data to enable wide-area Internet access for service providers and users. The article outlines the system used at the December 2000 IETF meeting and discusses its implications